Akumulasi Logam Berat Pb pada Karang Acropora aspera: Studi Pendahuluan - Panuntun, Putra; Yulianto, Bambang; Ambariyanto, Ambariyanto (977-2407769)
areas. The high human activity can lead to environmental degradation and coral reef ecosystems. One of the reasons is the heavy metal pollution. This present study aims to investigate on the accumulation of heavy metal Pb on the coral, Acropora aspera. The research was conducted at the Laboratory of Marine Science, Faculty of Fisheries and Marine Sciences, University of Diponegoro Semarang, Central Java. The method used is an experimental laboratory with coral A. aspera, using the heavy metal Pb with concentration 0.010 mg/l, and one control (0 mg/l). Coral, A. aspera was collected from Panjang Island. From this study it can be concluded that the coral A. aspera have capacities to accumulate heavy metals Pb. Accumulation of coral A. aspera significantly highest exposure of heavy metals Pb on day 10th.